Characterization of HVSR and VRSR in the Loess Plateau of China Based on Strong-Motion Data - Qi Li; Jingshan Bo; Da Peng (Applied Sciences)
In recent decades, China has collected extensive strong-motion data from the Loess Plateau, which is valuable for understanding the dynamic characteristics of loess sites and the effects of site conditions on seismic motions. The horizontal-to-vertical Fourier spectrum ratio (HVSR) and the horizontal-to-vertical velocity response spectrum ratio (VRSR) are widely used to study site dynamics. This study analyzes strong-motion data from the Loess Plateau to identify key features of the HVSR and VRSR curves. The results show that these spectral ratio curves effectively capture the dynamic behaviors of loess sites, minimizing the influences of earthquake magnitude and propagation path. While the spectral ratio peaks are less affected by magnitude, epicentral distance, and focal depth, they are significantly influenced by site conditions. Conversely, the dominant periods estimated from these curves are strongly influenced by magnitude, epicentral distance, and focal depth. For sites located on the Loess Plateau, the average amplification factor is approximately 3, with a mean predominant period of 0.4 s. These results provide valuable insights into the dynamic characteristics of loess sites and have practical implications for seismic design in the region.